Sistem Pelayanan Kesehatan Lansia Berbasis Web di Posyandu Lansia - Hilyah Magdalena; Hadi Santoso; Irene Chrismisel Tella (Jurnal ICT : Information Communication & Technology, 2022)
The elderly as part of the citizenry receive special attention, especially in the health sector, so that the welfare of the elderly will be better. The Elderly Posyandu is a form of government support for elderly health services. The Posyandu for the elderly, which is organized by the Puskesmas or Puskesmas Pembantu (Pustu), makes it easier for the elderly to check and maintain their health. The pandemic conditions that require us to always keep our distance and the limitations of manual administration services at the Posyandu, make this health service experience several obstacles such as repeated recording, difficulty accessing the schedule for the Elderly Posyandu, difficulty in finding data back from previous health checks, making drug prescriptions that are still very simple, and reporting difficulties related to posyandu for the elderly. These obstacles have prompted the need to develop a manual system into a web-based system. This web-based system for the elderly posyandu was developed using the Rapid Application Development (RAD) method. The web-based system allows the elderly to register from home and get medical cards that can be printed independently. The process of examining the elderly can be faster and diagnoses recorded systematically and accurately. Reporting is also easier to make because the data is already recorded in the database. The web-based elderly health service system for the Elderly Posyandu in Tepus Village also aims to protect the elderly from the potential for Covid-19 transmission by reducing queuing time and checking at the Posyandu.